BAGAIMANA KESEJAHTERAAN SUPIR BIS TERGANTUNG DUKUNGAN KELUARGA? - Hamdi, Muhammad Dudih Fadilah; Nurendah, Gemala (JURNAL PSIKOLOGI INSIGHT, 2019)
The purpose of this study was to examine the effect of family support perception on fatigue and subjective well-being of the bus drivers.  The research method used was a quantitative research with 125 bus driver participants. The instrument were Perceived Social Support from family or PSS-Fa (Procidano and Heller, 1983) to measure family support, Fatigue Measurement Scale or SPK to measure fatigue, Scale of Positive and Negative Experience (SPANE) instrument and Satisfaction With Life Scale (SWLS) to measure subjective well-being. Technique of data analysis was used simple regression. The results of this study indicated that family support affected fatigue with a significance level of 0.000 and family support influenced subjective well-being with  significance level of 0.01